Three soil chronosequences in recessional glacial deposits near the polar plateau, in the Central Transantarctic Mountains, Antarctica. Issue 5 (26th March 2014) - Scarrow, Joshua W.; Balks, Megan R.; Almond, Peter C.
Abstract Soil chronosequences in till deposits emplaced during glacial retreat in the Central Transantarctic Mountains are described. Discrepancies between the degree of soil development and reported cosmogenic surface exposure ages suggest slower, weaker soil development in this region than encountered in other areas of Antarctica. The study sites (Dominion Range, Mount Achernar and Ong Valley) were located between 83° and 85°S, at altitudes of 1600–2200 m, on the edge of the polar plateau. Soil landscape maps show a gradation of soil properties across landscape units that were designated as homogenous/single-event drifts in previous smaller-scale studies. Along transects away from the current ice edge, the depth to underlying ice thickened (from 2 cm to > 80 cm), soil became more weathered, saltier and less alkaline, and horizonation became more pronounced. Soil thickness, clast abundance and soil chemistry are all consistent with a two-layer mode of soil formation. We suggest that a thin, clast-rich surface horizon, originating from weathering of supraglacial debris, overlies a thick, clast-poor sublimation till. The supraglacial debris has a finite contribution to soil volume, whereas sublimation offers an ongoing source of soil material that thickens the soil from its base.